Comparison of Euphemism and Dysphemism Translation in Deutsche Welle (DW) Online News from English into Indonesia - Fadilla, Resica; Ardi, Havid (English Language and Literature, 2024)
This study uses translation techniques to compare euphemism and dysphemism translation from English into Indonesia in news articles on the Deutsche Welle (DW) online platform. The research employs a qualitative approach to identify the euphemism and dysphemism present in the source texts and to analyze the translation techniques used and their effect on the translation quality to convey these linguistic elements in the target language. The translation techniques are evaluated based on Molina and Albir's framework, while the translation quality is adapted from Nababan's framework. The findings indicate that the established equivalent is the most frequently used translation technique. Other techniques, such as modulation, generalization, and reduction, were found to have a more varied impact on the consistency and accuracy of the translations. This study highlights the importance of employing appropriate translation techniques to ensure that the intended meanings and effects of euphemism and dysphemism are effectively conveyed in the target language, especially in the context of news reporting. The insights gained from this research contribute to a deeper understanding of the challenges and strategies involved in translating sensitive linguistic elements and can serve as a valuable resource for translators, linguists, and educators in the field of translation studies.